Galactosamina influencia a percepção de aminoácidos, reduz a atividade de protease no intestino e aumenta a infecção de Lutzomyia longipalpis (Diptera: Psychodidae) por espécies de Leishmania - Tatiana Lima da Silva Fernandes (2018)
Leishmaniasis are a spectrum of neglected diseases that constitute a public health problem and are endemic in more than 88 countries, with an annual incidence of 1 to 1.5 million cases for the cutaneous forms and 500,000 new cases of visceral leishmaniasis. In Brazil, about 28,000 and 3,000 cases of cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL) are anually reported, respectively. Zoonotic Visceral Leishmaniasis, which is the most severe form of the disease, is caused in the New World by Leishmania infantum, which affects the liver, bone marrow and spleen of their vertebrate hosts. Lutzomyia longipalpis is the main vector of L. infantum in American countries and can be found from Mexico to Argentina. Male and female sandflies feed on carbohydrates, but females need to get a blood meal from vertebrates for egg maturation. As Leishmania develops exclusively within the gut of sandfly vectors, during blood digestion ingested parasites will have to survive the onslaught of digestive proteases. This study aimed to understand how Galactosamine (an amino sugar) interferes with sandfly digestive physiology. We used Galactosamine to manipulate the digestive physiology of L. longipalpis to investigate its influence on sandfly digestion and Leishmania development within their insect vectors. Galactosamine was able to reduce L. longipalpis trypsinolytic activity in a dose-dependent manner. This effect was specific for Galactosamine as other similar sugars were not able to affect sandfly trypsin production. An excess of amino acids supplemented with the blood meal plus 15 mM of Galactosamine was able to abrogate the reduction of the trypsinolytic activity caused by Galactosamine, suggesting that this phenomenon may be related to na impairment of amino acid detection by sandfly enterocytes. Galactosamine reduces sandfly oviposition, causes impact on sandfly longevity and specifically reduces sandfly gut proteases while increasing sandfly gut α-glycosidase activity. In an attempt to increase L. longipalpis susceptibility to two Leishmania species (L. mexicana and L. infantum) we performed artificial infections. Administration of 15 and 30 mM Galactosamine increased the number of promastigote forms of L. mexicana and L. infantum in insects treated with Galactosamine compared to their respective controls. Our results show that Galactosamine influences the detection of amino acids, reduces intestinal protease activity and benefits the growth of Leishmania within the L. longipalpis gut. Collectively, these results will help us to develop an experimental infection protocol to generate massively-infected sandflies to be used in challenges during vaccine trials, as sandfly bite is the ideal challenge to identify promising vaccine antigens, eliminating ineffective vaccine formulations before spending on the expensive and time consuming field tests.